WORKSHOP INTEGRASI PRINSIP KURIKULUM MERDEKA DALAM RENCANA PERKULIAHAN DI PROGRAM STUDI PGSD UNIVERSITAS MATARAM - Lalu Hamdian Affandi; Vivi Rachmatul Hidayati; Muhammad Erfan; Itsna Oktaviyanti; H. Husniati (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2023)
Try out of kurikulum merdeka is being implemented by schools. The trying out calls for participation of all components of education system. One key component of education system, that is teachers and teacher students, need to have deep understanding about curriculum implementation. The activity in this paper is intended as part of preparation for teacher students for implementing kurikulum merdeka in the future. The activity is aimed at developing semester lesson plans (Rencana Pembelajaran Semester-RPS) that are integrated with key concepts and principles of Kurikulum Merdeka. Participants of the activity are lecturers at Program Studi Pendidikan Guru Sekolah Dasar Universitas Mataram. Methods being implemented in this activity are lecturing, question-answer, group discussion, and group presentation. Results of the activity are points of kurikulum merdeka would be integrated into RPS are identified, whether as a method or as a content of student learning. Key aspects would be integrated into RPS are diagnostic assessment, differentiated instruction, learning target (Capaian Pembelajaran-CP), and product-oriented learning approach. Products of the activity are draft of RPS for several subjects, such as Pendidikan IPS SD, Pendidikan Matematika SD, and Pembelajaran Sains SD. The products indicated the insight of lecturers in PGSD about kurikulum merdeka. The insight represents intention to be followed by concrete actions in terms of learning activity and research needed to support curriculum theory development and effective practices for policy makers, teachers, and school principals.